ST-Segment Depression in Hyperventilation Indicates a False Positive Exercise Test in Patients with Mitral Valve Prolapse. (14th November 2010) - Michaelides, Andreas P.; Liakos, Charalampos I.; Antoniades, Charalambos; Tsiachris, Dimitrios L.; Soulis, Dimitrios; Dilaveris, Polichronis E.; Tsioufis, Konstantinos P.; Stefanadis, Christodoulos I.
Abstract : Objectives . Mitral valve prolapse (MVP) is a known cause for false positive exercise test (ET). The purpose of this study was to establish additional electrocardiographic criteria to distinguish the false positive exercise results in patients with MVP. Methods . We studied 218 consecutive patients (53 ± 6 years, 103 males) with MVP (according to echocardiographic study), and positive treadmill ET was performed due to multiple cardiovascular risk factors or angina-like symptoms. A coronary angiography was performed to detect coronary artery disease (CAD). Results . From 218 patients, 90 (group A) presented with normal coronary arteries according to the angiography (false positive ET) while the rest 128 (group B) presented with CAD. ST-segment depression in hyperventilation phase was present in 54 patients of group A (60%) while only in 14 patients of group B (11%), P < .05 . Conclusions . Presence of ST-segment depression in hyperventilation phase favors a false positive ET in patients with MVP.